"Evaluación de herbicidas de contacto y selectivo para el control de malezas invasoras en el cultivo de banano (Musa spp)". - Ortega Paredes, Galo Merino (2012)
This research was conducted during the dry season this year at the Finca "El Bosque", located in the Campus El Vergel, Valencia county, province of Los Rios. Star herbicides were tested (Glyphosate 480 g ai / L), non-selective systemic product * Tender Goal (oxyfluorfen 480 g ai / L), pre-emergent product, compared with the incidence of weeds in the trial arranged in a Designing randomized complete block (RCBD) with 4 replications and 5 treatments. The method used was designed to weed spraying, backpack pump boasts with a capacity of 20 liters. The number of applications was a single application at the time of initiating the investigation with application volume of 2.88 liters of water per plot commercial product of 144 m2 and the type of fan nozzle was 80-EF Series (8003 blue), has a flow rate of 0.86 l / min. The investigation took a total of twenty plots. We obtained the percentage of visual evaluación weeds in study walked "Rottboellia exaltata" straw donkey "goosegrass" and bermuda straw "Cynodon dactylon," based on the number of weeds per square meter, taking this in 5 locations randomized for each plot. It was concluded that: 1) The visual evaluación at 7 days was noted Goal * Tender (Oxyfluorfen 480 g ai / L) + Feature (Glyphosate 480 g ai / L) 1.50 0.50 l ha-1, with 5.56%. 2) At 15 days * highlighted Goal Tender (Oxyfluorfen 480 g ai / L) + Feature (Glyphosate 480 g ai / L) 1.50 0.50 l ha-1, with 14.85% in the evaluación rate visual weeds. 3) After 30 and.45 days in the result reached in the percentage of weed control was highlighted visual Star (Glyphosate 480 g ai / L) to 1.50 l ha-1, with 47.05%. 4) At 60 and 90 days in the percentage of weed evaluación was highlighted visual Goal * Tender (Oxyfluorfen 480 g ai / L) + Feature (Glyphosate 480 g ai / L) 1.50 0.50 l ha- 1, with 87.90 and 47.90% respectively.